2010
DOI: 10.1210/jc.2009-1954
|View full text |Cite
|
Sign up to set email alerts
|

Change in Amniotic Fluid Levels of Multiple Anti-Angiogenic Proteins before Development of Preeclampsia and Intrauterine Growth Restriction

Abstract: Significant elevation of leptin can be detected in AF 2 months earlier than the appearance of symptoms; thus, it may be used as a predictive marker for preeclampsia. The increase of these antiangiogenic proteins supports the roles of inflammation and oxidative stress in pathogenesis of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 71 publications
0
45
0
4
Order By: Relevance
“…29 In fact it is possible that the local vascular concentrations of ET-1 were even higher, since its secretion is polarized, and the circulating levels are usually lower. In a recent study, Wang et al 30 showed increased levels of ET-1 and sFLt-1 in the amniotic fluid obtained at 16-19 weeks of gestation in women who later developed PE, and noted a positive correlation between the two. Some limitations of this study must be acknowledged.…”
Section: Discussionmentioning
confidence: 95%
“…29 In fact it is possible that the local vascular concentrations of ET-1 were even higher, since its secretion is polarized, and the circulating levels are usually lower. In a recent study, Wang et al 30 showed increased levels of ET-1 and sFLt-1 in the amniotic fluid obtained at 16-19 weeks of gestation in women who later developed PE, and noted a positive correlation between the two. Some limitations of this study must be acknowledged.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11][12][13][14][15][16] Apart from being expensive, laboratories at majority of centers are not equipped with facilities of measurements of these markers. Measurement of maternal serum ferritin has also been used as a predictive marker of increase risk of IUGR.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100][101] Placental overproduction of soluble VEGF receptor-1 (soluble fms-like tyrosine kinase-1 [sFlt-1]), which inhibits VEGF signaling through trapping free VEGF, 102 causes maternal endothelial dysfunction and plays a central role in the pathogenesis of preeclampsia. 99,103,104 Intraamniotic sFlt-1 administration during late gestation impairs lung VEGF signaling and increases apoptosis of endothelial cells in newborn rats, which is followed by reductions in alveolarization and vascular growth, along with biventricular hypertrophy during infancy. 98 Similarly, intrauterine growth restriction has been associated with an increased risk for PH in BPD infants 105 and has also been associated with disruption of VEGF signaling and pulmonary vascular growth in experimental intrauterine growth restriction.…”
Section: Pvd In Bpdmentioning
confidence: 99%